2022
DOI: 10.3389/fmed.2022.904658
|View full text |Cite
|
Sign up to set email alerts
|

Are we ready to collaborate? The interprofessional collaborative competencies of healthcare professionals in the Global South context

Abstract: BackgroundCurrent evidence of interprofessional collaboration suggests the importance of measuring and identifying the current state of the health professions’ interprofessional competencies. Therefore, this study was aimed at measuring the interprofessional competencies of health professionals in the Global South context using the validated CICS29.Materials and methodsThis was a cross-sectional study involving 300 healthcare professionals of a newly established teaching hospital. Prior to the measurement of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Our study found that nurses' self-assessment based the three dimensions of the IPCPCS were highest in ICTF, which is followed by RCCC, and lowest in CLICR. Unlike IPC [22], CICS29 [25,30], JASSIC [34], and IPC-Thailand [32], the factors of leadership and conflict management were not mentioned. Recent empirical literature found that clear role functions and leadership, which have significant implications for IPCP core competencies, are influential factors in effective team collaboration [59].…”
Section: Construct Validity-principal-axis Factoring Of the Explorato...mentioning
confidence: 99%
“…Our study found that nurses' self-assessment based the three dimensions of the IPCPCS were highest in ICTF, which is followed by RCCC, and lowest in CLICR. Unlike IPC [22], CICS29 [25,30], JASSIC [34], and IPC-Thailand [32], the factors of leadership and conflict management were not mentioned. Recent empirical literature found that clear role functions and leadership, which have significant implications for IPCP core competencies, are influential factors in effective team collaboration [59].…”
Section: Construct Validity-principal-axis Factoring Of the Explorato...mentioning
confidence: 99%